Hereditary breast and ovarian cancer syndrome (BRCA) gene: Concept, pathways, therapeutics, and future - Anup Tamhankar; Tanuja Tamhankar (Indian Journal of Medical and Paediatric Oncology)
Hereditary breast and ovarian cancers are most commonly caused by mutations in BRCA1 and 2 genes. These are autosomal dominant mutations with high penetrance into subsequent generations. Affected individuals have deficiency in DNA repair mechanisms such as double strand DNA breaks (DSB) and non-homologous end joining (NHEJ). These tumors are peculiar due to early age of onset, typical histology such as triple negative breast cancers and high grade serous ovarian cancers and exquisite sensitivity to platinum analogues. These patients usually have better survival as compared to their wild type counterparts. Incidence of these mutations is rising due to better awareness about them amongst oncologists and patient population. Various genomic assays are available to detect germline and somatic BRCA mutations. Newer therapeutic frontiers like PARP inhibition have opened up due to better understanding of various mutations and their impact on subsequent pathways. Further studies are required to explore possibility of direct BRCA inhibition which may be useful in treatment of other solid organ cancers as well. This review focuses on understanding the pathophysiology of BRCA mutations, various pathways associated with the same, chemosensitivity patterns amongst affected cancer cells, targeted therapeutic opportunities and potential future developments in this field. We collected data from various published electronic records on google and have no conflicts of interest to be declared.